Halal Culture from an Ecotheological Perspective: An Ethnographic Study of the Madurese Community - Harisah Harisah; Nur Hidayah; Erika Amelia; Rahmawati Rahmawati (KARSA Journal of Social and Islamic Culture, 2026)
This research is a field study using an ethnographic approach that examines halal cultural practices from the perspective of Islamic eco-theology within Madurese society. The research focuses on two communities: Karang Penang Sampang Village and Lenteng Village in Sumenep Regency, Madura, which maintain traditional religious practices and resource management based on Sharia values and local wisdom. Data were collected through participatory observation, field documentation, and in-depth interviews with key informants, including religious leaders, traditional elders, women involved in cultural activities, local farmers, and young people active in the preservation of traditions. Research findings indicate that halal culture is understood not only as adherence to fiqh norms, but also as a form of ecological ethics that governs the relationship between humans and nature. For example, in the tradition â€œMÃ¨ngghulÃ¨,â€ in the lead-up to the Prophetâ€™s Birthday or Ramadan, communities engage in communal cooking rituals, using pesticide-free local ingredients, slaughtering animals in accordance with Islamic law, and serving food on natural containers such as banana leaves. Meanwhile, within the settlement system â€œTanean Lanjhangâ€, a pattern of collective life was discovered that reflects ecological and spiritual harmony through the management of water, land, and food based on family values. Values such as barokah (blessing), sakkena (peace), and the principle of al-halal bi thayyib serve as guidelines for the communityâ€™s social and ecological practices. This study shows that the halal culture in Madura is a manifestation of Islamic eco-theology that is contextual, sustainable, and rooted in local culture.